Perlakuan Akuntansi Persediaan Barang Dagangan Dan Pengaruhnya Terhadap Beban Pokok Penjualan - Aloisius Hama (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
Objectives to be achieved in this study is to know the accounting treatment of Merchandise Inventory which affects the Cost of Goods Sold on PT. Setia Makmur, Surabaya and can be used as input material of the company, to be able to use more accurate inventory method in determining Cost of Goods Sold in relation to Financial Statement. The accounting treatment for inventory is important for many companies, especially trading and manufacturing companies, as it has a significant effect on the presentation in the Balance Sheet and Income Statement. PT. Setia Makmur, Surabaya uses the Physical Method to record its inventory and LIFO Method (MTKP) to conduct an assessment of its Merchandise Inventory. The use of the Physical Method for the recording of Merchandise Inventory has a disadvantage from the point of internal control. The use of the LIFO Method (MTKP) in the Merchandise Inventory assessment is not in accordance with the Financial Accounting Standards which only allow the Special Identification Method, the FIFO Method (MPKP) and the Average Method. The mistake in choosing the right inventory valuation method will result in the presentation of Inventory, Cost of Goods Sold and Net Income which is overstated or understated.